Building Soft Skills for Village Officials: A Simulation-Based Public Speaking Training Approach - Rachmawati, Alifa Rizqia; S. Martono; Wartini, Sri; Permana, Made Virma; Sutrasmawati, Endang (Indonesian Journal of Devotion and Empowerment, 2025)
The regional autonomy program grants greater authority to local governments to manage their potential, improve public services, and encourage community participation. Ensuring public services are efficient and community-oriented poses distinct difficulties for village officials. Village officials’ service quality is significantly influenced by their competency. A lack of public speaking proficiency among village officials can obstruct effective message delivery and weaken public participation. This community service initiative aims to enhance the soft skills of village officials through public speaking training based on simulation method. This method enables participants to simulate situations similar to real-life conditions, enhancing comprehension, memory, and hands-on skills. The training combines oral teaching with hands-on practice, which is considered effective for experience-based learning. Training evaluation results indicate an improvement in participants’ understanding and skills related to fundamental public speaking techniques. The findings from this activity also emphasize the importance of training designs that are adaptive to participants’ needs, including the necessity for longer allocated time for simulation sessions and the use  of additional learning media such as representative public speaking practice videos. The sustainability of the program will be strengthened through additional competency training fit with field needs and involving Karang Taruna to form an inclusive and participatory public communication ecosystem from an early age.